Simple Synthesis of 2,4-Di(1-adamantyl)phenol - Mahboub, Radia; Benmansour, Abdelhafid; Mosset, Paul (Asian Journal of Chemistry, 2010)
2,4-Di(1-adamantyl)phenol was prepared from phenol and 1-bromoadamantane in chlorobenzene in the presence of copper(I) salts. CU(CH3CN)4PF6 has been found an efficient catalyst for this synthesis.